2016
DOI: 10.5539/gjhs.v8n10p9
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Psycho-Social Factors Affecting Women's Sexual Function during Pregnancy: A Narrative Review

Abstract: It is suggested that evaluation of sexual health during pregnancy must become a main pivot of routine prenatal care. In this way, it is necessary health care providers to be aware of a number of risk factors that may contribute to sexual dysfunction in pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Moreover, hormonal, physical and mental changes during pregnancy can affect women's sexuality and partnership characteristics. In this way, it is stated that women's sexual problems increase in the early months of pregnancy and return to the normal level during the postpartum period (9). However, there are inconsistencies in the studies' results with regard to the relationship between marital satisfaction and anxiety during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hormonal, physical and mental changes during pregnancy can affect women's sexuality and partnership characteristics. In this way, it is stated that women's sexual problems increase in the early months of pregnancy and return to the normal level during the postpartum period (9). However, there are inconsistencies in the studies' results with regard to the relationship between marital satisfaction and anxiety during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…So fact, many simultaneous physiological and psychological factors affect the sexual expression of the couples. Sexual fluctuations are a natural phenomenon during the transition to parenthood; couples must adjust to the new conditions and to the changes associated with sexuality during pregnancy, which are considered seasonal [29] and, Afrakoti NB, et al [30] classified these factors as biological, psychological and social factors. Meanwhile, Rivas RE, et al [31] found that the frequency of sexual activity declined progressively during pregnancy compared with pre-pregnancy levels, with a partial recovery six months after childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these changes, pregnancy and postpartum are sensitive periods that are frequently accompanied by changes in couples' sexual life. Sexual problems could affect women's personal and social life negatively, cause low self‐esteem, psychological problems, conflicts, and failure, and affect quality of life 3 . Impairment of psychological health is one of the most important risk factors for sexual dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual problems could affect women's personal and social life negatively, cause low self-esteem, psychological problems, conflicts, and failure, and affect quality of life. 3 Impairment of psychological health is one of the most important risk factors for sexual dysfunctions. Low sexual desire is strongly associated with depression.…”
Section: Introductionmentioning
confidence: 99%